Law Enforcement of Child Maltreatment Committed by Parents According to the Criminal Code - Inka Indah Pradani (Proceedings Series on Social Sciences & Humanities, 2023)
Violence against children committed by parents according to Law Number 35 of 2014 concerning child protection originates from cases of violence against children in Indonesia from time to time, which continue to occur and increasingly take various forms. As is known, children are the successors and assets owned by the nation that will maintain, and realize the ideals of the nation. Criminal acts are behaviors that violate the law, and sanctions will be given to the perpetrators who commit them. This problem is related to the factors that cause violence against children, and violence against children is not only caused by the factor of miseducation from parents. This article aims to find out what causes violence against children by parents and ways to prevent violence against children by parents. So it can be concluded that the factors that cause violence against children committed by parents are generally due to the negligence of parents and children themselves, economic factors, and environmental factors where the role of the community is lacking in preventing violence against children committed by parents.